Effects of Drought Levels on Soil Microbial Respiration and Biomass in Correspondence with Land use Types - Mai, Bui Hanh; Tu, Dang Thanh; Tam, Nguyen Duc; Hang, Tran Thi; Mai Van, Dinh; Anh, Luu The; Thi Thu Duyen, Hoang (VNU Journal of Science: Earth and Environmental Sciences; Vol 38 No 1DO - 10.25073/2588-1094/vnuees.4731, 2022)
Quang Nam province located in the middle of Vietnam, has suffered an increasing drought for many years, this threatens the crop production. Drought severity seems to be added in by land use change from forest to horticultural land but the interactions among drought, land use change and soil biological properties remain elusive in this area. Therefore, the research aimed to evaluate drought occurence in Quang Nam and also the effect of land use change on soil respiration and microbial biomass. Three hypotheses were proposed as i) Drought tends to be more severe in future in Quang Nam but behaves differently between plain and mountainous areas; ii) Microbial respiration reduces with increasing drought severity but depending on land use types; and iii) Water stress (60% to 30% water holding capacity - WHC) induces reduction of microbial biomass which remains no changes as soil moisture reduces from 30% to 10% WHC. Forest land decreased by 8.34% from 2003 to 2013 but increased by up to 5.86% in 2018 compared to 2013. Drought severity level has decreased slightly during 2003 - 2019 but more concentrated in the coastal plain than mountainous area, mainly occurred in the dry season from February to July. Basal respiration (BR) decreased a half as soil moisture declined from 60% to 30% WHC and remained unchange given the soil moisture decreased to 10% WHC. The dramatic decrease of BR demonstrated a shock of microbial community to altered environment condition. The similarity of BR between two soil types implied more important role of drought impacts than land use conversion. The decrease of soil moisture resulted in the reduction in nutrient diffusion that cause difficulties for microorganisms to approach available nutrients in soil and negatively affecting microbial biomass synthesis. Higher microbial biomass nitrogen (MBN) in forest than pineapple might suggest that forest soil would be of advantage to sustain soil fertility and microbial activities than crop land in resistence to drought impacts. Briefly, interdisciplinary approach is critical in assessment of climate change impacts on C and N cycles in correspondence to land use changes.